Plataforma ENCICLO: um Journal Club de Economia Circular - Gabriel dos Santos Correia (2024)
For the healthy advancement of cities and the planet as a whole, an urgent transformation towards sustainability is necessary, where the training of actors who will assist in this transition must be done quickly and effectively. Evidence-based practice (EBP), combined with a collaborative approach, proved to be a learning strategy capable of assisting this training. Therefore, this research proposes the design of an expanded model of a Journal Club (discussion group for scientific articles based on PBE), in Circular Economy - an approach to the mode of production and consumption that contemplates the sustainable development of the planet. It is expected that the results from these discussions will contribute to the establishment of digital learning platforms, with the potential to increase the reach of scientific research and dissemination of Circular Economy practices in cities.